Low cost proximate analysis of biomass for carbon production - Mokhtar, Robiatul Adawiyah; Hussin, Faizah; Mohd Salleh, Mohamad Amran; Saliban, Hairulizam; Idris, Azni; Wan Ab. Karim Ghani, Wan Azlina; Razali, Siti Zulaika; Mat Nong, Mohd Ali (Program Pemindahan Ilmu - Kementerian Pendidikan Malaysia, 2013)
This study look at how UPM can help Hakita Engineering Sdn Bhd to capitalize on the big market for activated carbon which is about RM5 billion/year. The price of carbon depends on the quality which is determined by the selection of source materials and technique of carbonization. The analysis of carbon can be costly; therefore a simple technique is needed. In this project UPM team has trained and transferred the knowledge and skill to determine biomass and carbon quality to HESB. Palm Kernel Shells were selected in this study. During training, proximate analysis was conducted in two techniques, modern and simple technique using ash tray. TGA proximate analysisshowed60%, 0.01% and30.8% while simple proximate analysis using ashtray showed 54.73%,3.13%, and 38.12% for volatile matter, ash content and fixed carbon contents. Graduate interns have also been exposed to company environment in constructing pilot scale continuous carbonizer.